Rucaparib: a PARP inhibitor for the treatment of advanced ovarian cancer - Babu, Merin; C. J., Josini (International Journal of Basic & Clinical Pharmacology, 2017)
Ovarian cancers arise from the uncontrolled growth and replication of epithelial cells of the surface of ovary which constitutes 90% of cases. PARP (poly ADP-ribose polymerase) inhibitors are a novel type of therapy that prevents cancer cells from repairing their DNA which have been damaged by other chemotherapeutic agents. Rucaparib is a novel drug that was approved by the US FDA in 2016 for the treatment of patients with deleterious BRCA mutation associated advanced ovarian cancer. Inhibition of the PARP enzymes leads to the increased formation of PARP-DNA complexes which results in DNA damage, apoptosis and cell death. Nausea, fatigue including asthenia, vomiting, anemia, abdominal pain, constipation, decreased appetite, diarrhea, thrombocytopenia and dyspnea were the common adverse effects seen among rucaparib users. Even though, the drug may cause myleodysplastic syndrome/ acute myeloid leukemia (MDS/AML) it remains as novel therapeutic target for the treatment of advanced ovarian cancer involving BRCA mutation.